Assessment of Ponseti technique of manipulation and serial casting in idiopathic clubfoot - Khazi Syed, Asif Hussain; Koppolu Kanthi, Kiran Kumar; Baroothu, Yakub; Chodavarapu, Lalith Mohan (International Journal of Research in Orthopaedics, 2019)
Background: Congenital talipes equinovarus is one of the commonest congenital foot deformities. Ponseti technique of treatment of clubfoot has gained popularity in the last few decades. Feet treated by Ponseti technique are supple, flexible and pain free. We have treated congenital idiopathic clubfoot with Ponseti technique at our institute and present our results. Methods: Forty eight feet in thirty children with clubfoot were treated by Ponseti technique in our institute. The study was conducted from December 2013 to December 2015. Parents were counselled regarding treatment protocol and maintenance with bracing was closely monitored. Each child was followed up for a minimum of six months. Pirani score was used to objectively document progress of treatment. Results: The average number of casts required for complete correction was 6.6. 38% feet required tendoachilles tenotomy. Higher the initial Pirani score, more number of casts were required to achieve full correction. Number of casts needed for complete correction did not correlate to time of presentation. Conclusions: Ponseti method is very effective in correcting congenital idiopathic clubfoot deformity. It’s easy to learn, is inexpensive and can completely correct the deformity. In developing nations, well trained Orthopaedic surgeons can treat these children effectively and decrease disabled population.